STABILISASI HARGA BUNGA MAWAR UNTUK MENJAGA KETAHANAN EKONOMI PETANI PADA MASA PANDEMI COVID-19 DI DUKUH KALIWULUH, CLUNTANG, MUSUK, BOYOLALI - YOGA SETYO UTOMO; JUJUK JUHARIAH; ALEAN KISTIANI H.S (KRIDA CENDEKIA, 2021)
One of the potentials in Dukuh Kaliwuluh, Cluntang Village, Musuk District, Boyolali Regency is a lot of roses that grow both in the yard and on agricultural land. However, the unstable price of rose flowers caused the economic stability of the farmers in the hamlet to be disturbed because roses were one of the farmers' daily sources of income. Therefore, student work program during the Community Service Program that is carried out independently focuses on increasing the stability of the price of roses. The aim of this program is to increase the resilience of the community economically to face the Covid-19 pandemic. The methods implemented are: coordination, outreach, and reporting. The impact of this activity is that the community becomes more creative in handling rose yields so that the economic value of roses can be more stable.